Peran Guru Pendidikan Agama Islam: Pembentukan Karakter dan Peningkatan Prestasi Siswa - Ikbal Ramadhani, Muhammad; Afendi, Achmad Ruslan (INCARE, International Journal of Educational Resources, 2025)
This study aims to find out the role of Islamic Religious Education (PAI) in shaping the character of students and improving the learning achievement of grade VIII students at MTs Nashirul As'adiyah. The background of this research is the importance of character formation and academic achievement as an indicator of educational success, especially through PAI learning. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation. The subjects of the study were PAI teachers and grade VIII students. Data analysis techniques include data reduction, data presentation and drawing conclusions. The results of the study show that PAI teachers have a strategic role in shaping the character of students through example, habituation, and delivery of applicable religious materials. In addition, PAI learning activities that are integrated with moral and spiritual values have a positive impact on improving student learning achievement. Thus, Islamic Religious Education contributes significantly in shaping religious, disciplined, and responsible character as well as in encouraging students to achieve better achievements.